HIV-associated neurocognitive disorder and HIV-associated myelopathy in a patient with a preserved CD4, but high viral load-a rarely reported phenomenon: a case report and literature review - Biniyam Alemayehu Ayele; Wondwossen Amogne; Lalise Gemechu (BMC Infectious Diseases, 2020)
Abstract Background Despite widespread use of combination antiretroviral therapy (cART), HIV-associated neurocognitive disorder (HAND) and HIV-associated myelopathy (HAM) are not showing significant reduction in there occurrence. The HAM is a progressive myelopathy that often occur synchronously with severe form of the HAND in patients’ having advanced immunosuppression. However, co-existence of less severe form of the HAND and HAM in patient with relatively preserved CD4 cells is rarely reported clinical entity in post cART era. Case presentation We report a 16-year old male, acquired HIV infection vertically, was on second line regimen because of virological failure since 3 years. His current CD4 lymphocyte count is 835 cells/uL with viral RNA level of 33,008 copies/mL. Currently presented with progressive forgetfulness, gait imbalance, and a frequent staring episodes without loss of postural tone. Neurological examination was pertinent for cognitive dysfunction with score of 6 on International HIV Dementia Scale (motor speed = 3, psychomotor speed = 2, and memory recall = 1). Lower limbs power is 4−/5, increased deep tendon reflexes, and unsteady gait. Brain MRI revealed diffuse both cortical and white matter T2 and FLAIR hyperintense lesions. Thoracic MRI showed abnormal T2 signal prolongation spanning from mid thoracic cord to conus. Electroencephalography study showed severe generalized slowing with evidence of focal dysrhythmia in bilateral frontotemporal regions. Unremarkable serum vitamin B 12 level (286 ng/mL). Virological failure with the HAND, HAM and seizure was considered. Dolutegravir +3TC + ATV/r regimen and valproate for seizure disorder was started. On 6 months follow up evaluation, he is clinically stable with significant improvement of his symptoms related to seizure disorders and modest improvement of his cognitive dysfunction, as he is now attending his school regularly. However, less improvement was observed reading his gait abnormality. Conclusion This case supports the current understanding regarding the persistent occurrence of HIV-associated neurocognitive disorder and HIV-associated myelopathy even decades after introduction of cART. Therefore, it’s important to screen HIV+ patients for the HAND and HAM even if they have relatively preserved immunity. Because patient can be easily shifted to ART drugs with better CNS penetrating potential to achieve acceptable virological suppression level, to observe sound clinical improvement.